Salt tolerance evaluation in guava germplasm - Thaipong, K.; Boonprakob, U. (International Journal of Agricultural Technology, 2019)
The five-month-old plants obtained from stem-cutting of 20 guava genotypes were grown in sand culture with 200 mM NaCl for 19 days to evaluate their salt tolerance. The primary symptom of salt stress, leaf burn, appeared from the young to the mature and from the margin to the center of leaves in all genotypes were reported. Based on leaf burn severity, the 20 guava genotypes were separated into four groups by level of tolerance. One genotype (KUHP38) was highly tolerant, three genotypes (‘Paen Seethong’, ‘Na Suan’, and KUHP12) were moderately tolerant, eight genotypes were sensitive, and eight genotypes were highly sensitive to salt stress. The highly tolerant genotype showed high survival and slight leaf burn, while the highly sensitive genotypes showed severe leaf burn and even death of some plants. Sodium and chloride content in the leaves, stems, and roots of the highly sensitive genotype was higher than in the highly tolerant genotype. Based on the results obtained, ‘Paen Seethong’ and ‘Na Suan’ were recommended for desert-type commercial plantings in the saline soil regions of Thailand, while KUHP38 and KUHP12 may be used as rootstocks. These genotypes could be used as breeding materials for developing new cultivars with high salt tolerance.